Calculations of factors that affect thermal conductivity in epoxy composites with hybrid carbon nanotube and graphene nano platelet - Han Wang; Ercong Xiao; Taotao Fan; Xiaotuo Li; Wenkai Xiao (Materials Research Express, 2020)
Carbon Nanotubes (CNTs) and Graphene Nano Platelets (GNPs) had been used to enhance the thermal conductivity of the epoxy composites and show a synergistic effect. Complex service conditions also put forward the requirements for the structural design of the composites to get better performance. Researches should be done to further understand the mechanism of enhancement in composites and find ways to assist the design and optimization of the structure. In this research, epoxy composites with CNTs, GNPs and hybrid CNTs-GNPs (5:2) were prepared, whose total content of fillers was kept constant at 0.4 vol%. Test of specific surface area shew the hybrid fillers had less aggregation and the composites with hybrid fillers had the highest thermal conductivity. Observing the microstructure of the composites, CNTs were absorbed on the surface of GNPs, forming a cross-network which could improve aggregation and provide channels for the heat. A series of finite element models were established using scripts to find the factors that affect the forming of network and heat flow. A parameter was created to reflect the distribution of the fillers: distance of non-network(DNN). Positions, orientations, ratios, shapes, and sizes are all factors. The effect of angles depends on the relative positions of the fillers. A proper bending degree of CNTs would have better enhancement. The vertical-structure network was created manually and heat flux on the network was shown: GNPs expanded the area of network for the acceptance and release of heat. CNTs provide efficient channels for the multidirectional heat flow. The combination of the geometry expanded the influence region of the network.